Implementation of the Qur’an and Hadith as Educational Sources in the World of Islamic Education - Nur, Muhammad; AM, Rusydi; Charles, Charles (TOFEDU: The Future of Education Journal, 2022)
This article scrutinises the Al-Qur’an and Hadith as a source of Islamic education which is a reference and way of life for Muslims. However, there are still many worlds of Islamic education that have not fully implemented the Qur’an and Hadith as real sources (Syamil Mutakammil) in Islamic education, except only dwelling on symbols, discourses and studies. So, Islamic religious education should actually refer to the pattern of prophetic education, by prioritizing the role of exemplary and learning models based on the formation of faith and morals and the concept of brotherhood which is full of values, as the educational model applied by the Prophet when he was in Mecca and Medina. Thus, there is an equivalence of normative quality and applicative quality in values ​​and meanings